What do morphological data tell us about the Andean-Neotropical Gripopteryginae (Plecoptera: Gripopterygidae) and related taxa? - Duarte Simoes, Tacio Vitor (2025)
The Gripopterygidae family, a diverse group of stoneflies (Plecoptera) endemic to the Southern Hemisphere, has traditionally been divided into five subfamilies, though the monophyly of most remains uncertain due to limited morphological and molecular sup-port. Here we conducted a morphology-based cladistic analysis using 50 characters and 41 taxa, including representatives from all five Gripopterygidae subfamilies and three Austroperlidae species, to test the monophyly of Gripopteryginae and determine the phylogenetic position of a newly discovered species, Tupiperla furcata sp. nov. The analysis, rooted with Penturoperla barbata (Austroperlidae), employed parsimony with implied weighting and tree bisection reconnection methods. Results supported a core Gripopteryginae clade, with absence of a posterior sclerite in tergum 10, but excluded Neopentura semifusca, which was more close-ly related to Antarctoperlinae. Additionally, Paragripopteryx munoai presented morphological divergence, suggesting it may require reclassification into a new genus. These results challenge the current subfamily classifications, particularly Dinotoperlinae and Lep-toperlinae, and highlight the need for further taxonomic revision. To advance the understanding of Gripopterygidae phylogeny, we suggest incorporating molecular data and expanding taxon sampling throughout the Southern Hemisphere. Such efforts would clarify evolutionary relationships and biogeographic patterns, paving the way for a more robust classification of Plecoptera.